PRESENTING ENTERPRISE ARCHITECTURE STRATEGIES USING BUSINESS MODEL CANVAS (CASE STUDY OF E-COMMERCE PT XYZ) - Chintamy Christini; Basuki Rahmad (Faculty of Computer Science Universitas Indonesia, 2015)
Information Technology (IT) is known as enabler of business. One of the study that align business and IT is enterprise architecture. In this era, one of the business that become a trend the world is electronic commerce (e-commerce). With the suitable enterprise architecture strategies, e-commerce can be improved according to the business and IT condition. This paper represents about study case of an Indonesian e-commerce website which is still unknown by internet users and the SWOT strategy analysis using Business Model Canvas. Finally, there is a creation of enterprise architecture strategies that will support e-commerce business for give a better business to Indonesian society.